Bibliometric Analysis of Cathepsin B Research From 2011 to 2021 - Yang, Xiaoli; Yin, Hua; Zhang, Deyu; Peng, Lisi; Li, Keliang; Cui, Fang; Xia, Chuanchao; Li, Zhaoshen; Huang, Haojie (Frontiers in Medicine, 2022)
Cathepsin B (CTSB) is a kind of functional lysosomal protein implicated in the progression of various diseases. A large number of CTSB-related studies have been conducted till date. However, there is no comprehensive bibliometric analysis on this subject. In our study, we performed quantitative analysis of CTSB-related publications retrieved from the Science Citation Index Expanded (SCIE) of the Web of Science Core Collection (reference period: 2011-2021). A total of 3062 original articles and reviews were retrieved. The largest number of publications were from USA (n=847, 27.66%). The research output of each country showed positive correlation with gross domestic product (GDP) (r=0.9745, P<0.0001). Active collaborations between countries/regions were also observed. Reinheckel T and Sloane BF were perhaps the most impactful researchers in the research landscape of CTSB. Plos One was the most prevalent (119/3062, 3.89%) and cited journal (3021 citations). Comprehensive analysis of the top citations, co-citations, and keywords was performed to acquire the theoretical basis and hotspots of CTSB-related research. The main topics included CTSB-related cancers and inflammatory diseases, CTSB-associated cell death pattern, and the applications of CTSB. These results provide comprehensive insights into the current status of global CTSB-related research in pancreas, which is worthy of continued follow-up by practitioners and clinicians in this field.